Reflexiones en torno a la didáctica: implicaciones en la formación docente - Bejarano Gutiérrez, Sandra; Castro Villalobos, María de los Ángeles; Hernández Segura, Ana María; Herrera Castro, Ana; Oviedo Madrigal, Gabriela; Ruiz Guevara, Susana; Vargas León, Rosario (Revista Electrónica Educare, 2004)
This paper derives from reading about and analyzing how didactics is conceptualized, as well as the its implications in teacher training. It presents background information for the area of didactics and current issues on the problems of the area. In addition, we include some didactic assumptions that are necessary to take into account in teacher training.